PEMBIMBINGAN DENGAN MODEL PeTiS NaSi UNTUK MENINGKATKAN KEMAMPUAN GURU MELAKUKAN TERAPI RELIGI - Nur (Universitas Nahdatul Ulama Surabaya, 2020)
This research was conducted through teacher guidance using Pe Tis Na Si model which intended to improve the teachers’ ability to practice religious therapy to the students. The steps of this model are planning, training at school or work place, practicing at school based on the schedule, reflected together for further correction. The approach of this research is qualitative which uses descriptive method. The instruments in this research are questionnaire, observation sheet and testimonial. The questionnaire was given to the teachers before guidance and after practicing. The observation sheet was used during the guidance process and during the religious therapy process. Testimonial was given by the teachers and the appointed students. Based on the data analysis of questionnaire result of the initial meeting, 100 % of the participant teachers never did the similar therapy before. After guiding in the first session, the mean score of the teachers’ ability was 66,1. It was in the good category. In the second session, the mean score of the teacher’s ability increased into 88,4. If it was compared, the increase from the first session to the second session was 23 %. Based on the result of testimonial given by the teachers, most of the teachers stated that this activity was very helpful for the teachers’ behavior themselves and the students. Based on the testimonial given by the students, the students stated that this activity aroused their awareness about their mistakes and changed their behavior towards their parents better such as having more spirit to study. The conclusion of this activity was religious therapy guidance using Pe Tis Na Si model could improve the teachers’ ability to conduct religious therapy to the students. The teachers were more confident and enthusiastic to practice it at their schools.